The highly reintegrative approach of electronic monitoring in the Netherlands. (April 2017) - Boone, Miranda; van der Kooij, Matthijs; Rap, Stephanie
This contribution describes the way electronic monitoring (EM) is organized and implemented in the Netherlands. It will become clear that the situation in the Netherlands is characterized by, in particular, two features. The application of EM is highly interwoven with the Probation Service and its reintegrative objectives, a characteristic that dominates the organization and use of EM to a great extent. Paradoxically, EM is hardly used in the Netherlands as an autonomous (stand-alone) replacement for short prison sentences. The most straightforward explanation for this situation is that the Netherlands does not really need EM to replace prison capacity since its prison population already decreased drastically since 2005. A second explanation is that the intense involvement of the probation service in the enforcement of electronic monitoring has as a side-effect that these sanctions are not accepted as punitive sanctions, but fully framed into the rehabilitative perspective.